2016
DOI: 10.1371/journal.pone.0153812
|View full text |Cite
|
Sign up to set email alerts
|

Glucose and Glycogen Metabolism in Brugia malayi Is Associated with Wolbachia Symbiont Fitness

Abstract: Wolbachia are endosymbiotic bacteria found in the majority of arthropods and filarial nematodes of medical and veterinary importance. They have evolved a wide range of symbiotic associations. In filarial nematodes that cause human lymphatic filariasis (Wuchereria bancrofti, Brugia malayi) or onchocerciasis (Onchocerca volvulus), Wolbachia are important for parasite development, reproduction and survival. The symbiotic bacteria rely in part on nutrients and energy sources provided by the host. Genomic analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 46 publications
4
46
0
Order By: Relevance
“…From a nutritional standpoint, an elevated abundance of proteases and proteasome subunits is consistent with the possibility of increased amino acid availability for Wolbachia ( 79 ). The upregulation of glycogen phosphorylase complements recent work using Brugia malayi nematodes, which indicated that Wolbachia bacteria induce the upregulation of glycolytic enzymes ( 80 ). An increased local availability of pyruvate is hypothesized to benefit Wolbachia ( 81 ).…”
Section: Discussionsupporting
confidence: 80%
“…From a nutritional standpoint, an elevated abundance of proteases and proteasome subunits is consistent with the possibility of increased amino acid availability for Wolbachia ( 79 ). The upregulation of glycogen phosphorylase complements recent work using Brugia malayi nematodes, which indicated that Wolbachia bacteria induce the upregulation of glycolytic enzymes ( 80 ). An increased local availability of pyruvate is hypothesized to benefit Wolbachia ( 81 ).…”
Section: Discussionsupporting
confidence: 80%
“…Additionally, the ratio of protein to carbohydrate intake modulated Wolbachia abundance in Drosophila 43 . Glucose metabolism and glycogen storage in B. malayi are linked with Wolbachia fitness in a metabolic co-dependency pathway shared between the bacteria and its nematode host 44 . In the B. malayi system, w Bm lacked genes for 2 glycolytic enzymes, 6-phosphofructokinase and pyruvate kinase, and were unable to convert glucose into pyruvate 44 .…”
Section: Discussionmentioning
confidence: 99%
“…In the mutually exclusive association between Wolbachia and filarial nematodes, evidence indicates that Wolbachia plays a role in heme provisioning [ 27 , 28 ], while directly relying on host pyruvate production, through glycolysis, for its own survival. Removal of Wolbachia via antibiotic treatment led to increased host levels of glucose and glycogen [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%